2019
DOI: 10.1038/s41396-019-0436-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial succession on decomposing root litter in a drought-prone Scots pine forest

Abstract: Decomposition is a major flux of the carbon cycle in forest soils and understanding the involved processes is a key for budgeting carbon turnover. Decomposition is constrained by the presence of biological agents such as microorganisms and the underlying environmental conditions such as water availability. A metabarcoding approach of ribosomal markers was chosen to study the succession of bacterial and fungal decomposers on root litter. Litterbags containing pine roots were buried in a pine forest for two year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 130 publications
12
55
0
Order By: Relevance
“…After transplantation, fast-growing Ascomycota dominated, and then were replaced by earlystage ectomycorrhizal fungi. Previous studies looked at the mycorrhizal succession in pine seedlings (Peay et al, 2011;Herzog et al, 2019;Rudawska et al, 2019), and we found that the shift of root associated fungi in our study followed the general trend, despite being inoculated with T. matsutake.…”
Section: Change Of Fungal Communities In Pine Seedlings After Transplsupporting
confidence: 70%
“…After transplantation, fast-growing Ascomycota dominated, and then were replaced by earlystage ectomycorrhizal fungi. Previous studies looked at the mycorrhizal succession in pine seedlings (Peay et al, 2011;Herzog et al, 2019;Rudawska et al, 2019), and we found that the shift of root associated fungi in our study followed the general trend, despite being inoculated with T. matsutake.…”
Section: Change Of Fungal Communities In Pine Seedlings After Transplsupporting
confidence: 70%
“…Indeed, microbe-derived functions, such as metabolites in this study, directly translate to human applications ( 47 ). The link between taxonomic and functional changes has previously been observed also in other systems such as in soils ( 48 , 49 ). As such, it is of great significance to study community differences and link them to functioning to evaluate the functional consequences of observed community changes in any studied system.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, it is helpful to simplify complex communities into individual taxa to determine and focus subsequent analyses on functionally important keystone species ( 59 , 60 ). In comparison to commonly performed whole-community analyses ( 8 , 48 , 61 ), the method based on indicator microorganisms and metabolites can accurately reflect changes in environmental conditions. Our indicator taxon approach to determine the key factors driving community and functional changes not only could reveal differences much more strongly but even allowed accurate modeling of temporal changes in taxonomically important microorganisms and functional metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…(b) root exudates are also an important source of organic carbon input into soil, especially in actively growing plants (De Deyn, Cornelissen, & Bardgett, 2008;Herzog et al, 2019); (c) greater plant coverage decreases carbon loss by wind erosion (Zhou, Li, Chen, Zhang, & Li, 2011). Previous studies have shown that the richness loss of specific bacterial and eukaryotic taxa can further increase the growth of a few fast-growing and more competitive microbes (Fierer et al, 2012;Fierer, Bradford, & Jackson, 2007;Li, Rui, Mao, Yannarell, & Mackie, 2014).…”
Section: Fencing Increased Bacterial and Eukaryotic Abundancementioning
confidence: 99%